2017
DOI: 10.21826/2446-8231201772205
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia polínica de espécies epífitas de Cactaceae Juss. do Rio Grande do Sul, Brasil

Abstract: RESUMO -Neste trabalho é apresentado o estudo sobre a morfologia polínica de 11 espécies da família Cactaceae, com hábito epífi to, ocorrentes no Rio Grande do Sul, extremo sul do Brasil, com descrições, medidas, fotomicrografi as, bem como informações ecológicas e biogeográfi cas. Os grãos de pólen possuem tamanhos variáveis (médios, grandes e gigantes), com formas prolato-esferoidais a prolatos; aberturas 3-colpados (Lepismium cruciforme (Vell.) Miq. e Rhipsalis cereuscula Haw.) e 6-colpados (demais espécies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
8
0
5
Order By: Relevance
“…as medium-sized, spherical, and tricolporate, with elongate endoaperture and pointed echinae. Cancelli et al (2010) analyzed three Calea species ( C. clematidea Baker, C. kristiniae Pruski, and C. pinnatifida ). Cancelli et al (2010) considered that the species of Calea present 12 echinae in equatorial view, a different result from that found here for the species of Calea sect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…as medium-sized, spherical, and tricolporate, with elongate endoaperture and pointed echinae. Cancelli et al (2010) analyzed three Calea species ( C. clematidea Baker, C. kristiniae Pruski, and C. pinnatifida ). Cancelli et al (2010) considered that the species of Calea present 12 echinae in equatorial view, a different result from that found here for the species of Calea sect.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous palynological studies have been conducted on Asteraceae (Gonçalves-Esteves 1976, 1977a, 1977b; Gonçalves-Esteves and Esteves 1986, 1988a, 1989a, 1989b; Mendonça et al 2002; Cancelli et al 2005, 2010; Magenta et al 2010; Moreira et al 2019; Reshmi and Rajalakshmi 2019; Ulukuş and Tugay 2020; Marques et al 2021; Souza-Souza et al 2021, 2022; Tellería et al 2023). However, there are no specific papers describing the palynology of the tribe Neurolaeneae, only studies focused on Asteraceae that evaluated the pollen of some Neurolaeneae species: Calea species (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Kurtz (1963) in his study of pollen in Cactaceae – which included several genera in Hylocereeae – identified relevant variation in pollen size in Hylocereus and Selenicereus , differences in the number of furrows in a number of genera such as Weberocereus , and useful variation in pollen sculpture in the length of spinules and perforation of the exine in several genera. Likewise, the identification of species in Cactaceae using pollen in countries such as Brazil, Peru and Argentina found useful characters such as variation in size, shape, and exine thickness to determine taxa at tribe and genus levels (Santos and Watanabe 1996; Santos et al 1997; Garralla and Cuadrado 2007; Cuadrado and Garralla 2009; Lattar and Cuadrado 2010; De la Cruz et al 2013; Miesen et al 2015; Cancelli et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pollen morphology of Cactaceae was first studied by Kurtz Jr. (1948;1963) who continued over 110 genera and about 700 species as well as Leuenberger (1976) and some other regional reviews (HEUSSER, 1971;CUADRADO & GARRALLA, 2009;RAMÍREZ, 2012;BAUERMANN et al, 2013;GARRALLA et al, 2013;CANCELLI et al, 2017) among others. The Cactaceae family is taxonomically difficult, presenting problems in the delimitation of genera and species, and the circumscription of many taxa shows inconsistences due to the variation of the morphological characters (JUDD et al, 2009).…”
Section: Introductionmentioning
confidence: 99%